The Understanding of Small and Medium Enterprises on Creating Shared Value in Indonesia: An Exploratory Study - Gina Harventy; Abdul Hamid , Fatima; Mat Yassin, Fatimah; Binti Mokhtar, Norsyahida (Universitas Muhammadiyah Yogyakarta, 2025)
Implementing the Creating Shared Value (CSV) strategy is a new strategy to respond to sustainability issues. The CSV strategy can be used to solve social and environmental problems while creating economic value for companies and society. CSV has been widely applied by large companies, but its understanding and implementation among Micro, Small, and Medium Enterprises (SMEs) in developing countries, especially in Indonesia, are still limited. This study aims to explore SMEs' understanding of the CSV concept, identify driving factors, and uncover challenges and obstacles in implementing CSV in SMEs in Indonesia. This study utilized a case study approach with a semi-structured interview method with 9 SMEs listed on the Indonesia Stock Exchange. The study shows that most SMEs still equate the definition of CSV with Corporate Social Responsibility (CSR), and do not fully understand its strategic potential as an intangible asset as a competitive advantage for SMEs. CSV drivers in SMEs include company competitiveness, economic and social value, and business strategy. However, SMEs face challenges and obstacles in implementing CSV. Lack of expertise and guidelines indicates a lack of knowledge, expertise, and clear guidance in implementing CSV strategically in SMEs. This study emphasizes the importance of CSV integration in SME business strategies and provides theoretical and practical contributions to the development of policies that encourage CSV adoption in SMEs in Indonesia.